Transcriptome sequencing reveals the potential mechanisms of dietary lutein regulation on chicken leg muscle development - Tuanhui Ren; Meng Xu; Wujian Lin; Wen Luo; Xiquan Zhang (Poultry Science)
ABSTRACT: Lutein is an antioxidant that can indicate the oxidative status of organisms through its coloration and may be involved in the development process of chicken skeletal muscle. In this study, after feeding Nanhai Yellow Chickens with lutein-containing feed for 21 d, the lutein group significantly increased the muscle fiber diameter and decreased the fiber density in the chicken's leg muscles compared to the control group. To elucidate the potential regulatory mechanisms by which lutein is involved in muscle development, RNA-seq was used to detect changes in gene expression in chicken leg muscle tissue. After data analysis, a total of 249 significantly differentially expressed genes (DEG) were identified, including TGF-β superfamily (MSTN and TGFB1) and nonreceptor tyrosine kinase c-Src (SRC). Results from GO and KEGG analysis showed that the DEGs were enriched in GO terms such as positive regulation of the ERK1/ERK2 cascade and negative regulation of myoblast differentiation, as well as signaling pathways including the Toll-like receptor signaling pathway and the MAPK signaling pathway. These significantly enriched GO terms and pathways are closely related to muscle development, suggesting that lutein may play an important role in the process of chicken muscle development. This study provides insights into the regulatory mechanisms of dietary lutein on chicken muscle development.